Optimal Portfolio Formation With Single Index Model And Magic Formula - Syamsul Wongosari; Syamsu Alam; Fauzi R. Rahim (SEIKO : Journal of Management & Business, 2023)
The purpose of this research is to determine the optimal portfolio using the single index model and magic formula method. The research period is the LQ 45 index stocks that are on the Indonesian Stock Exchange in the period April 2020 to April 2023.This study uses a quantitative descriptive research design that aims to provide a detailed description of the optimal portfolio of stocks. The research sample determined in this research was for the period April 2020 to April 2021 as many as 35 shares, for the period April 2021 to April 2022 as many as 36 shares, and for the period April 2022 to April 2023 as many as 35 shares. The results of the calculations of the two methods will be compared with market returns. The portfolio formed is adjusted every year where portfolio performance is measured using the sharpe ratio. Results obtainedthe single index model portfolio provides an annual average return of 82.45 % far greater than the Magic Formula Portfolio which generates a return of 13.96 %. These two Portfolio methods outperformed the LQ 45 market return of 11.76% but the IHSG market return of 15.11% was higher than the Magic Formula portfolio return. The Single Index Model portfolio risk (35.97%) is higher than the magic formula portfolio risk (14.32%), while the IHSG risk (9.74%) is lower than the two portfolio methods, but the LQ 45 risk is 14.99 % higher than the Magic Formula risk and lower than the Single Index Model risk. Keywords: single index model; magic formulas; index sharpe; LQ 45; optimal portfolio